2015
DOI: 10.1038/srep08260
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism analyses of 30 InDels in Chinese Xibe ethnic group and its population genetic differentiations with other groups

Abstract: In the present study, we obtained population genetic data and forensic parameters of 30 InDel loci in Chinese Xibe ethnic group from northwestern China and studied the genetic relationships between the studied Xibe group and other reference groups. The observed heterozygosities ranged from 0.1704 at HLD118 locus to 0.5247 at HLD92 locus while the expected heterozygosities ranged from 0.1559 at HLD118 locus to 0.4997 at HLD101 locus. The cumulative power of exclusion and total probability of discrimination powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The values of the power of exclusion (PE), the matching probability (MP), the typical paternity index (TPI), and the polymorphic information content (PIC) ranged from 0.0067 to 0.2231, 0.3524 to 0.8379, 0.5488 to 1.0826 and 0.0814 to 0.3742, respectively. The lowest HO, HE, PIC, TPI, PD and PE were observed at HLD 118 locus, and this locus was also found with the lowest polymorphism in other previously studied groups10. The combined power of exclusion (CPE) and discrimination (CPD) at the 30 InDel loci in the Tujia group were 0.9860 and 0.9999999999761, respectively; combined matching probability (CMP) value of 30 InDels in the group was 2.3894 × 10 −11 , higher than that in our previous study which reached 1.10974 × 10 −19 of 21 autosomal STRs in Tujia group11.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The values of the power of exclusion (PE), the matching probability (MP), the typical paternity index (TPI), and the polymorphic information content (PIC) ranged from 0.0067 to 0.2231, 0.3524 to 0.8379, 0.5488 to 1.0826 and 0.0814 to 0.3742, respectively. The lowest HO, HE, PIC, TPI, PD and PE were observed at HLD 118 locus, and this locus was also found with the lowest polymorphism in other previously studied groups10. The combined power of exclusion (CPE) and discrimination (CPD) at the 30 InDel loci in the Tujia group were 0.9860 and 0.9999999999761, respectively; combined matching probability (CMP) value of 30 InDels in the group was 2.3894 × 10 −11 , higher than that in our previous study which reached 1.10974 × 10 −19 of 21 autosomal STRs in Tujia group11.…”
Section: Resultssupporting
confidence: 75%
“…D A distances between the 16 groups with each other based on allelic frequencies of the 30 InDel loci were shown in Table 2. Short genetic distances were found between the Tujia group and Shanghai Han17, Guangdong Han18, South Korean23, Beijing Han9, Xibe10, She17, Tibetan9, and Yi16 groups; and further distances were observed between the Tujia group and Chinese Kazak9, Uigur9 groups; whereas the larger distances were estimated with Uruguayan24, Dane25, Central Spanish26, Basque26, and Hungarian populations27. Pairwise populations had small genetic distances, which indicated that they had close genetic relationships or shared a recent common ancestor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCA and admixture analysis are the most commonly used approaches to investigate genetic relationships between populations. They have been applied to multiple InDel datasets in previous studies [20,42,44]. Similar to the analysis of F ST s, results of the PCA and admixture analysis showed significant genetic homogeneity between Hui and East Asian populations.…”
Section: Discussionmentioning
confidence: 90%
“…A study on mitochondrial DNA reported by Yu et al also revealed that the Xinjiang Xibe group had a close relationship with the Chinese Korean group and the northern and southern Han groups, and the relationship between the Xibe and Korean group was closer than that between the Xibe and the two Han groups [6]. A study of 30 insertion-deletion markers showed that the Xibe group was first clustered with a South Korean group, followed by Beijing Han and Guangdong Han groups, and then the Tibetan group [7]. The Xibes lived in northeastern China prior to being moved along with other ethnic minorities to Xinjiang by the Qing government in order to consolidate and reinforce the northwestern border defenses in the mideighteenth century [8].…”
mentioning
confidence: 98%